KAWIN PAKSA DALAM PANDANGAN KIAI KRAPYAK - Kurniawan, Arif (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2016)
The writings that discuss the practice of forced marriage signifies that the forced marriage is still massively implemented in the community. The phenomenon of forced marriage is right using religious arguments. Forced marriages in fiqh known as ijbār rights. Forced marriage can be a manifestation of the right ijba̅r if the requirements are met in determining ijba̅r, and if it is not in accordance with these concepts then a forced marriage positioned as ikrah. This paper specifically discusses the forced marriage in perspective of Kiai Krapyak. The view of Kiai Krapyak toward forced marriage with opposing views literally. But essentially the view of Kiai Krapyak tend to be similar. They agree that forced marriages should as much as possible to be avoided, though, in the law of Islam , the practice of forced marriages are a valid contract. Islamic law does not condone a forced marriage which connotes as ikrah, although the majority of schools of fiqh agree for the ijbār rights. The majority of schools of fiqh agree that they have their rights with a different perspective of the school of one sect to another. Positive law mentions the consent of both couples as a necessity, then automatically there is no compromise on the permissibility of execution of forced marriage.[Tulisan-tulisan yang membahas tentang kawin paksa menandakan bahwa praktek atau pelaksanaan perkawinan paksa masih masif di kalangan masyarakat. Fenomena kawin paksa menjadi ritus dengan menggunakan hujah agama. Kawin paksa dalam fiqh dikenal dengan istilah hak ijbār.  Kawin paksa bisa jadi manifestasi dari hak ijba̅r apabila terpenuhi syarat-syarat dalam menentukan ijba̅r, dan apabila tidak sesuai dengan konsep tersebut maka kawin paksa diposisikan sebagai ikrah. Tulisan ini khusus membahas tentang kawin paksa dalam perspektif Kiai Krapyak. Pandangan Kiai-kiai Krapyak terhadap kawin paksa mempunyai pandangan yang berbeda secara literal. Akan tetapi secara esensial pandangan para Kiai Krapyak cenderung sama. Mereka sepakat bahwa kawin paksa sebisa mungkin untuk dihindari, meskipun dalam prakteknya kawin paksa merupakan akad yang sah. Hukum Islam tidak membenarkan adanya kawin paksa yang berkonotasi ikrah, kendatipun mayoritas mazhab fiqh sepakat adanya hak ijbār. Mayoritas mazhab fiqh sepakat adanya hak tersebut dengan perspektif yang berbeda antara mazhab satu dengan mazhab yang lain. Hukum positif menyebutkan persetujuan kedua pasangan sebagai suatu keharusan, maka secara otomatis tidak ada kompromi terhadap kebolehan  pelaksanaan kawin paksa.]